IMPACT ANALYSIS OF GREEN ECONOMY INSTRUMENTS ON SUSTAINABLE NATURAL RESOURCE MANAGEMENT - Karauwan, Welky; Taruming, Denny Adri; Kampilong, Joni Kutu’; Arina, Kristi Karla; Pangkey, Deisy Agnes Pertiwi Juita; Maramis, Pingkan Aprilia; Lintong, Elsje Hanna (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
The implementation of Green Economy Instruments (GEI) is crucial for achieving Sustainable Natural Resource Management (SNRM), particularly in agrarian regions facing environmental degradation. This study aims to evaluate the effectiveness of GEI, including carbon tax, emission trading system, renewable energy subsidies, and fiscal incentives, in promoting SNRM among farming business actors in Tomohon, North Sulawesi. A quantitative approach was employed using Structural Equation Modeling (SEM) with Smart PLS 4.0, based on survey data from 500 respondents. The results indicate that most GEI dimensions have a positive influence on SNRM, with an R² value of 0.847. Fiscal Policy Instruments (FPI) and Environmental Regulations (ERS) showed the most substantial impact. At the same time, Carbon Tax (CT) and Sustainable Financing (SF) exhibited significant but negative relationships, suggesting potential misalignment between policy design and local perception. This research presents a new conceptual framework “Policy Effectiveness in Agrarian Settings” emphasizing that the success of GEI depends on perceived benefits, accessibility, and visible outcomes. The findings offer practical implications for regional policymakers, highlighting the importance of targeted fiscal support, clear regulations, and enhanced communication to promote the adoption of green policies. Additionally, this study fills a gap by providing empirical insights into the application of GEI outside urban or industrial contexts, thereby supporting the achievement of SDG 12, SDG 13, and SDG 15. Future studies should explore longitudinal effects and stakeholder perceptions through qualitative methods to deepen understanding of policy barriers and opportunities.